Regulation of extracellular matrix In patients with Q-wave myocardial infarction after thrombolytic therapy - V. D. Syvolap; S. M. Kyselov (Zaporozhye State Medical University, 2014)
Aims. In order to study the levels of matrix metalloproteinase-9, tissue inhibitor of metalloproteinase-1, intracardiac hemodynamics, frequency of acute cardiac aneurysm development in patients with Q-wave myocardial infarction after thrombolysis, 74 patients were examined. Methods and results. All participants underwent clinical and laboratory examination, echocardiography, determination of serum levels of matrix metalloproteinase-9 and tissue inhibitor of metalloproteinase-1. Conclusion. Patients, who got thrombolysis in 6 to 12 hours period, had excessive activation of the proteolysis system on the background of relative defi cit of tissue inhibitor of metalloproteinase-1, the prevalence of dilatation and restrictive diastolic dysfunction, cardiac aneurysm was detected frequently and thrombogenic potential was higher.